‘I’d be in my school uniform’: the informal curriculum of street harassment - Fileborn, B.; Hardley, Jess (2023)
A growing body of literature has documented the pervasive occurrence of harassment in schools, and street-based harassment. However, to date there has been little attention to street-based harassment occurring in school-related contexts, such as walking to and from school in uniform. In this article, we aim to address this gap by exploring findings from 47 qualitative interviews with individuals who have experienced street and public harassment in Australia. Street harassment was commonly encountered by participants while they were in their school uniform, and beginning high school was often associated with the onset or increased intensity of street harassment. Drawing on Foucault’s concept of disciplinary power and feminist theorisation on embodiment, we argue that street harassment–and school responses to this harassment–functioned as an ‘informal curriculum’ that normalized the occurrence of harassment and produced young people’s bodies as sites of risk that required surveillance, control, and careful management through engagement in safety work.